Studies on dried/smoked barracuda - Balachandran, K.K., Joseph, A.C., Prabhu, P.V. and (Fishery Technology, 2021)
Physical, chemical and organoleptic characteristics of dried and smoked barracuda (Sphyraena spp.) during storage at ambient temperature are reported. Initial increase in total volatile basic nitrogen (TVBN) content after drying as well as smoking did not have any significant effect on the organoleptic qualities of the products. Smoking was found effective in delaying the onset of fungal attack and also in improving the organoleptic qualities.